2019
DOI: 10.1002/jppr.1450
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ attitude, self‐reported knowledge and practice of dosage adjustment among chronic kidney disease patients in Malaysia

Abstract: Drug-related issues, such as inappropriate drug dosing, are pervasive patient issues that are particularly common among chronic kidney disease (CKD) patients. Pharmacists have the expertise to play an important role in avoiding such problems. The aim of the present study was to explore pharmacists' self-perceived knowledge, attitude and practice towards dosage adjustment among CKD patients. A cross-sectional, Web-based, self-administered survey was conducted among 1594 registered pharmacists in Malaysia. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
3
2
0
Order By: Relevance
“…Given the scope of their roles, clinical pharmacists, especially those in inpatient settings, frequently engage in medication reviews and dose adjustments. These findings mirror the results from a study conducted in Malaysia [ 10 ]. Our data also revealed that chief pharmacists showcased a notably higher attitude score than other pharmacists.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Given the scope of their roles, clinical pharmacists, especially those in inpatient settings, frequently engage in medication reviews and dose adjustments. These findings mirror the results from a study conducted in Malaysia [ 10 ]. Our data also revealed that chief pharmacists showcased a notably higher attitude score than other pharmacists.…”
Section: Discussionsupporting
confidence: 89%
“…Their vast experience usually involves diverse training programs and the use of various decision support tools. This aligns with existing literature, suggesting that training, expert clinical support, and a robust clinical decision support system can mitigate drug-related issues in CKD patients [ 10 , 31 ]. Moreover, the perception scores were significantly higher among resident pharmacists.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Notably, failures in dosage adjustments compound treatment costs and lengthen hospital stays, placing further strain on both patients and healthcare infrastructures [43] . Past research has indicated that between 25-77% of drugs, which required dosage modifications, were adjusted improperly [45,46] . Many such drugs, crucial for CKD patients, are routinely disregarded, inviting health complications [44] .…”
Section: Introductionmentioning
confidence: 99%